Broadband in School: Impact on Student Performance - Belo, Rodrigo; Ferreira, Pedro; Telang, Rahul (Management Science, 2014)
This paper examines the effects of providing broadband to schools on students' performance. We use a rich panel of data on broadband use and students' grades from all middle schools in Portugal. Employing a first-differences specification to control for school-specific unobserved effects and instrumenting the quality of broadband to account for unobserved time-varying effects, we show that high levels of broadband use in schools were detrimental for grades on the ninth-grade national exams in Portugal. For the average broadband use in schools, grades reduced 0.78 of a standard deviation from 2005 to 2009. We also show that broadband has a negative impact on exam scores regardless of gender, subject, or school quality and that the way schools allow students to use the Internet affects their performance. In particular, students in schools that block access to websites such as YouTube perform relatively better. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2013.1770 . This paper was accepted by Lorin Hitt, information systems.